UTILIZATION OF INFORMATION TECHNOLOGY IN FINANCIAL DECISION-MAKING: ANALYSIS ON MANAGEMENT INFORMATION SYSTEMS - Hadi Supratikta; Tuti Hasanah; Livio Agung Dharmaesta (PT. Jurnal Center Indonesia Publisher, 2024)
Effective and efficient financial decision-making is a crucial element in the success of organizations in today's digital era. This study aims to explore how the utilization of information technology in management information systems (MIS) influences the financial decision-making process within an organization. Researchers analyzed how the integration of information technology in MIS helps financial managers in collecting, managing, and analyzing financial information to support timely and accurate decision-making. This study employed a qualitative descriptive method using secondary data sources collected through a literature review and document analysis. The findings indicate that the application of information technology in MIS has had a positive impact on the financial decision-making process, including increased data accessibility, faster and more accurate analysis, and a better understanding of the organization's financial conditions. The practical implications of these findings include the importance of investing in adequate information technology infrastructure and developing competent human resources in managing management information systems. This study provides significant contributions to our understanding of the role of information technology in enhancing the quality of financial decision-making in a rapidly changing and increasingly complex business environment